Pengaruh Pola Asuh Orang Tua Terhadap Kenakalan Remaja Di SMA Negeri Plus Sukowono - Aisah, Siti; Parawansa, Khofifah Indar; Salsabilla, Nandina Putri; Fitriana, Ani Qotuz Zuhro’ (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Juvenile delinquency is now occurring in almost every corner of the country, especially to children who are still in school, as happened at SMA Negeri Plus Sukowono, juvenile delinquency that occurs is smoking and truancy during class. One of the factors that causes juvenile delinquency is parenting style. Parenting patterns of parents who cannot adjust to the needs of children then affect social development in their environment. Parenting parents consist of authoritarian parenting, displacement parenting, and permissive parenting. The parenting style that causes delinquency at SMA Negeri Plus Sukowono is Permissive and Authoritarian Parenting. The purpose of this study was to find out how the parenting style of the parents towards juvenile delinquency at SMA Negeri Plus Sukowono. The research method used in this study was to use a quantitative descriptive approach, the respondents consisted of 34 young students of class X with a sampling technique using simple random sampling, and the collection used a questionnaire. The formulation of the problem that will be taken in this research is is there any influence of parenting style on juvenile delinquency?, how is the effect of parenting style on juvenile delinquency?, and what are the factors that influence juvenile delinquency?.